GC/MS and FAB/MS analysis of lipid molecules for taxonomic classification of microorganisms - Miketová, Petra; Khailová, Ludmila; Jelinek, David; Schram, Karl H.; Moore, Ida M. (Ki); Vytřasová, Jarmila (Univerzita Pardubice, 2005)
The goal of this project was to identify the presence of microorganisms in the environment by using their gas chromatography/mass spectral (GC/MS) characteristics as biomarkers. A combination of GC/MS results and pattern recognition statistical evaluation were used to provide a mathematical model with defined parameters for different microorganisms, which allows the organisms to be classified as bacterial, fungal or viral nature. Results from fast atom bombardment mass spectral (FAB/MS) analysis showed differences in the complex lipid profiles for most of the analyzed microorganisms. A general screening method that can provide early detection of microorganisms would permit initiation of most therapeutics. Various drugs are used to treat bacterial, fungal or viral diseases and, when treatment is started early, there is a dramatic reduction in mortality. A methodology for detection and classification of microorganisms is described in this paper.
Keywords: plynová chromatografie; Hmotnostní spektrometrie; mikroorganismy; Klasifikace; Tuky